0144 Sick leave patterns as predictors of disability pension or long-term sick leave: A 6.75-year follow-up study in municipal eldercare workers. (23rd June 2014) - Stapelfeldt, Christina; Vinther Nielsen, Claus; Trolle Andersen, Niels; Krane, Line; Borg, Vilhelm; Fleten, Nils; Jensen, Chris
Abstract : Objectives: The public health care sector is challenged by high sick leave rates among home-care personnel. This group also has a high probability of being granted a disability pension. We studied whether a workplace-registered frequent short-term sick leave spell pattern was an early indicator of future disability pension or future long-term sick leave among eldercare workers. Method: 2774 employees' sick leave days were categorised: 0–2 and 3–17 short (1–7 days) spells, 2–13 mixed short and long (8+ days) spells, and long spells only. Disability pension and long-term sick leave were subsequently identified in a National register. The cumulative incidence proportion as a function of follow-up weeks was estimated using the Kaplan-Meier curve. The relative cumulative incidence (RR) of experiencing one of these events within 352 weeks was analysed in a generalised linear regression model using the pseudo values method adjusted for age, occupation and unfavourable work factors. Results: A frequent short-term and a mixed sick leave pattern increased the RR of being granted a disability pension; the RR was 2.08 (95% CI: 1.00–4.35) and 2.61 (95% CI: 1.33–5.12). Inversely, the long-term sick leave pattern was not associated with a significantly increased RR compared with a non-frequent short-term pattern. The risk of long-term sick leave was significantly increased (1.35–1.64 (95% CI: 1.12–2.03) for all sick leave patterns beyond 0–2 short spells. Conclusions: Sick leave length was a better indicator of future workability than spell frequency. Preventive actions should target employees engaged in home-care having sick leave spells exceeding seven days, irrespective of spell frequency.